Modal transformation of nonstationary electromagnetic field in unbounded nonlinear medium - Думин, А. Н.; Ахмедов, Р. Д. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2018)
Transient processes in nonstationary electromagnetic field for nonlinear medium are considered. All electric and magnetic field components are received by evolutionary approach to transient electrodynamics as functions of space-time domain. The analysis of field components and numerical approach for further field calculation are proposed. Transient effects in the problem of radiation into stationary homogeneous medium of plane disk of homogeneously distributed electric current are considered. The iterative method of nonlinearity accounting is demonstrated on this example. Self-effects generated by secondary sources of electromagnetic field in its propagation process in the medium are considered.